Conductive MPPO material based on carbon fibers and preparation method thereof

By introducing modified flame retardant and modified toughener into the conductive MPPO materials based on carbon fiber, and adopting the double-screw extruder granulation process, the problem of insufficient flame retardant performance of the existing materials is solved, and the excellent conductivity, impact resistance, heat resistance and flame retardant performance of the materials is achieved, extending the service life and environmentally friendly advantages.

CN119662009AActive Publication Date: 2025-03-21JIANGXI PLASTIC HIGH-TECH MATERIALS CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510175006.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-18
Publication Date
2025-03-21
Estimated Expiration
2045-02-18

AI Technical Summary

Technical Problem

In actual applications, existing conductive MPPO materials based on carbon fiber have insufficient flame retardant performance and are difficult to meet higher environmental protection and performance requirements.

Method used

By preparing a carbon fiber-based conductive MPPO material containing a modified flame retardant and a modified toughening agent, the modified flame retardant is prepared by reacting compounds such as toluene, aniline, 2-allyl-4-methylphenol and paraformaldehyde. The modified toughening agent is prepared by copolymerizing materials such as tetra-(4-aminophenoxy)methylmethane and N-methylpyrrolidone, and the material is granulated by a twin screw extruder.

Benefits of technology

It achieves excellent conductivity, impact resistance, heat resistance and flame retardant properties of the material, extends the service life of the material, and has the advantages of environmental protection and sustainable development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to a conductive MPPO material based on carbon fibers and a preparation method of the conductive MPPO material, and belongs to the technical field of high polymer materials. The conductive MPPO material based on the carbon fibers comprises the following components in parts by weight: 40-70 parts of PPO resin, 10-30 parts of polystyrene, 5-20 parts of a modified flame retardant, 2-10 parts of a modified flexibilizer, 0.1-5 parts of an antioxidant, 0.5-2 parts of a lubricant and 5-15 parts of the carbon fibers, benzoxazine in the modified flame retardant forms a carbon layer, oxygen and heat are isolated, non-combustible gas is released, combustion is retarded, the high glass transition temperature endows heat resistance, and polydopamine cooperates with phosphorus and nitrogen to interrupt a combustion chain; flexible phenoxy in the modified flexibilizer enhances the toughness, maleimide and silica improve the impact resistance, and a flexible silica chain segment improves the tensile strength; the carbon fiber-based conductive MPPO material prepared by the invention not only has good conductive and impact-resistant effects, but also has excellent heat resistance and flame retardance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a conductive MPPO material based on carbon fiber and a preparation method thereof. Background Art

[0002] Polyphenylene ether (PPO) is one of the world's five major general-purpose engineering plastics, with good mechanical properties, heat resistance and non-toxic properties. However, pure PPO resin has low electrical conductivity, and the products are prone to stress cracking and low notch impact strength.

[0003] With the progress of science and technology and the development of industry, the blending application of PPO and polystyrene (PS) has been promoted to prepare PPO / PS alloy, namely MPPO. MPPO has low density, convenient processing, water resistance, temperature resistance, good dimensional stability, and is widely used in office equipment, household appliances, electronic products and the automotive industry. With the increasing awareness of environmental protection and the trend of high-performance miniaturization of electronic products, MPPO materials need to meet higher requirements, not only requiring high impact strength, but also improving heat resistance. In addition, although the conductive MPPO material based on carbon fiber has certain flame retardancy, with the increase in actual application requirements, its own flame retardancy no longer meets the requirements. Therefore, the research and development of excellent conductive MPPO materials based on carbon fiber has important practical significance and application value. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a carbon fiber-based conductive MPPO material and a preparation method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions: A conductive MPPO material based on carbon fiber and a preparation method thereof, comprising the following raw materials in parts by weight: 40-70 parts of PPO resin, 10-30 parts of polystyrene, 5-20 parts of modified flame retardant, 2-10 parts of modified toughening agent, 0.1-5 parts of antioxidant, 0.5-2 parts of lubricant, and 5-15 parts of carbon fiber; The antioxidant is antioxidant 1010; The lubricant is N,N-ethylene bisstearamide.

[0006] The modified flame retardant is prepared by the following method: Step A1: Mix toluene, aniline, 2-allyl-4-methylphenol and paraformaldehyde evenly, stir thoroughly, heat to 90° C., and react for 5 hours to obtain an intermediate product; Further, the usage ratio of toluene, aniline, 2-allyl-4-methylphenol, and paraformaldehyde is 75-150 mL: 0.1-0.2 mol: 0.1-0.2 mol: 0.2-0.4 mol; Under the action of paraformaldehyde, the hydroxyl group of 2-allyl-4-methylphenol and the amino group of aniline are firstly reacted to synthesize an intermediate product containing a benzoxazine structure; Step A2: 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, N,N-dimethylformamide and the intermediate product were mixed, stirred at 150° C. for 9 h, filtered, washed, and vacuum dried at 60° C. for 24 h to obtain a pre-product; Further, the usage ratio of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, N,N-dimethylformamide, and the intermediate product is 6.48-10.8 g: 40-60 mL: 0.03-0.05 mol; Secondly, the carbon-carbon double bond of the intermediate product is combined with 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to generate a pre-product; Step A3: the pre-product, tris(hydroxymethyl)aminomethane) and deionized water were mixed, the pH was adjusted to 8.5, dopamine hydrochloride was added, ultrasonic treatment was performed for 30 minutes, stirring was performed at room temperature for 24 hours, vacuum filtration was performed, washing was performed, and vacuum drying was performed at 60° C. for 24 hours to obtain a modified flame retardant; Further, the dosage ratio of the pre-product, tris(hydroxymethyl)aminomethane, deionized water, and dopamine hydrochloride is 6-8 g: 5-10 g: 500-900 mL: 2.4 g; Finally, dopamine hydrochloride is self-polymerized on the surface of the pre-product to generate polydopamine to prepare a modified flame retardant.

[0007] The modified toughening agent is prepared by the following method: Step B1: Tetrakis-(4-aminophenoxy)methylmethane and N-methylpyrrolidone were mixed at 0°C under nitrogen protection, stirred evenly, and then maleic anhydride was added, and stirred at 0-15°C for 1 hour to obtain product a; Further, the usage ratio of tetrakis-(4-aminophenoxy)methylmethane, N-methylpyrrolidone, and maleic anhydride is 0.625-1.25 g: 5 mL: 0.49-0.98 g; Under the catalysis of N-methylpyrrolidone, maleic anhydride and the amino group of tetrakis-(4-aminophenoxy)methylmethane were reacted to obtain product a; Step B2: dodecylbenzenesulfonic acid and deionized water were mixed, the temperature was raised to 45°C, and the mixture was stirred evenly. Then, decamethylcyclopentasiloxane and 3-allyloxypropyltrimethoxysilane were slowly added dropwise, the mixture was mixed evenly, and the mixture was reacted for 3 hours. The mixture was cooled to room temperature to obtain product b. Further, the dosage ratio of deionized water, decamethylcyclopentasiloxane, and 3-allyloxypropyltrimethoxysilane is 45 mL: 3-5 mol: 5-7 mol, and the dosage of dodecylbenzenesulfonic acid accounts for 1.4% of the total amount of deionized water in the system; Then, H + , opening the ring of decamethylcyclopentasiloxane to form a growth chain, and condensing with 3-allyloxypropyltrimethoxysilane to obtain product b; Step B3: Mix product a and product b, stir for 10 minutes, then add azobisisobutyronitrile and ethanol and mix evenly, heat to 70-80°C, react for 3 hours, and cool to room temperature to obtain a modified toughening agent; Further, the usage ratio of product a, product b, azobisisobutyronitrile, and ethanol is 5-7 g: 2-4 g: 0.34-0.52 g: 20 mL; Finally, the modified toughening agent is prepared by copolymerizing the carbon-carbon double bonds of product a and product b.

[0008] A method for preparing a conductive MPPO material based on carbon fiber specifically comprises the following steps: S1. Mixing PPO resin, polystyrene, modified flame retardant, modified toughening agent, antioxidant and lubricant to prepare a mixed material; S2. Add the mixed material and carbon fiber into a twin-screw extruder for extrusion and granulation to obtain a conductive MPPO material based on carbon fiber, wherein the temperature of the twin-screw extruder is set to: zone 1: 180-200°C, zone 2: 280-320°C, zone 3: 280-320°C, zone 4: 280-320°C, zone 5: 280-320°C, zone 6: 240-260°C, zone 7: 240-260°C, zone 8: 240-260°C, head temperature: 260-280°C, and the screw speed is 400-600r / min.

[0009] Beneficial effects of the present invention: The carbon fiber-based conductive MPPO material of the present invention has good conductivity and impact resistance effects, and also has excellent heat resistance and flame retardancy, thereby extending the service life of the material.

[0010] The benzoxazine structure in the modified flame retardant prepared by the present invention is a benzo-heterocyclic compound containing nitrogen and oxygen six-membered heterocyclic rings, which has good heat resistance and flame retardancy, forms a dense carbon layer during the combustion process, effectively isolates oxygen and heat, and releases non-combustible gas at the same time, reduces the oxygen concentration in the combustion area, and slows down the combustion rate. Due to its high glass transition temperature, no small molecules are released during the curing process, and the shrinkage rate is low, the modified flame retardant has excellent heat resistance; at the same time, polydopamine is rich in phenolic hydroxyl groups and amino groups, and can react with free radicals at high temperatures to interrupt the combustion chain and further enhance the flame retardant effect. It has high thermal stability and can maintain its structure at high temperatures, thereby delaying thermal decomposition of the material. In addition, the phosphorus-nitrogen flame retardant 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, as a phosphaphenanthrene compound with high thermal stability, promotes the formation of a dense and continuous carbon layer during combustion, and synergizes with polydopamine to effectively isolate oxygen and heat, inhibit combustion, and synergizes with the phosphorus-oxygen double bond to achieve flame retardancy, thereby extending its service life. In addition, the modified flame retardant prepared by the present invention is halogen-free, which helps to reduce pollution to the environment and damage to the ecosystem, is harmless to human health, and achieves sustainable development. The modified toughening agent prepared by the present invention, with its advantages of macromolecular polymer, shows performance that surpasses traditional small molecule toughening agents. In the modified toughening agent, tetrakis-(4-aminophenoxy)methylmethane can significantly improve the toughness of PPO and polystyrene, enhance the bonding force between polymer molecules, improve the toughness of resin, enhance the cross-linking density of cured products, and thus enhance the impact resistance due to the presence of multiple amino groups and flexible phenoxy groups; at the same time, the maleimide structure generated by its reaction with maleic anhydride has high flexibility, enhances the flexibility of the material molecular chain, forms an interpenetrating network, relieves stress concentration under external force, and synergizes with silicon oxygen bonds to further enhance the impact resistance; in addition, the flexible -Si-O-Si-segment in the polymer has high bond energy and large bond angle, which can not only maintain stability, but also relieve the internal thermal stress of the resin, improve the tensile strength of the resin, and comprehensively optimize the toughness and impact resistance of the material. DETAILED DESCRIPTION

[0011] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0012] Embodiment 1: A method for preparing a conductive MPPO material based on carbon fiber, specifically comprising the following steps: S1. Weigh the raw materials by weight: 40 parts of PPO resin, 10 parts of polystyrene, 5 parts of modified flame retardant (prepared in this embodiment), 2 parts of modified toughening agent (prepared in this embodiment), 0.1 parts of antioxidant, 0.5 parts of lubricant, and 5 parts of carbon fiber; mix PPO resin, polystyrene, modified flame retardant, modified toughening agent, antioxidant 1010 and N,N-ethylene bisstearamide to obtain a mixed material; S2. Add the mixed material and carbon fiber into a twin-screw extruder for extrusion granulation to obtain a conductive MPPO material based on carbon fiber, wherein the temperature of the twin-screw extruder is set to: zone 1: 180°C, zone 2: 280°C, zone 3: 280°C, zone 4: 280°C, zone 5: 280°C, zone 6: 240°C, zone 7: 240°C, zone 8: 240°C, die head temperature: 260°C, and the screw speed is 400r / min; The modified flame retardant is prepared by the following method: Step A1: 75 mL of toluene, 0.1 mol of aniline, 0.1 mol of 2-allyl-4-methylphenol and 0.2 mol of paraformaldehyde were mixed evenly, stirred thoroughly, heated to 90° C., and reacted for 5 h to obtain an intermediate product; Step A2: 6.48 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 40 mL of N,N-dimethylformamide and 0.03 mol of the intermediate product were mixed, stirred at 150° C. for 9 h, filtered, washed, and dried under vacuum at 60° C. for 24 h to obtain a pre-product; Step A3: 6 g of the pre-product, 5 g of tris(hydroxymethyl)aminomethane) and 500 mL of deionized water were mixed, the pH was adjusted to 8.5, 2.4 g of dopamine hydrochloride was added, ultrasonic treatment was performed for 30 min, stirring was performed at room temperature for 24 h, vacuum filtration and washing were performed, and vacuum drying was performed at 60° C. for 24 h to obtain a modified flame retardant; The modified toughening agent is prepared by the following method: Step B1: 0.625 g of tetrakis-(4-aminophenoxy)methylmethane and 5 mL of N-methylpyrrolidone were mixed at 0° C. under nitrogen protection, stirred evenly, and then 0.49 g of maleic anhydride was added, and stirred at 0° C. for 1 h to obtain product a; Step B2: Mix dodecylbenzenesulfonic acid and 45 mL of deionized water, raise the temperature to 45°C, stir evenly, then slowly drop 3 mol of decamethylcyclopentasiloxane and 5 mol of 3-allyloxypropyltrimethoxysilane, mix evenly, react for 3 hours, and cool to room temperature to obtain product b. The amount of dodecylbenzenesulfonic acid used accounts for 1.4% of the total amount of deionized water in the system; Step B3: Mix 5 g of product a and 2 g of product b, stir for 10 min, add 0.34 g of azobisisobutyronitrile and 20 mL of ethanol and mix evenly, heat to 70° C., react for 3 h, and cool to room temperature to obtain a modified toughening agent.

[0013] Embodiment 2: A method for preparing a conductive MPPO material based on carbon fiber, specifically comprising the following steps: S1. Weigh the raw materials by weight: 55 parts of PPO resin, 20 parts of polystyrene, 12 parts of modified flame retardant (prepared in this embodiment), 6 parts of modified toughening agent (prepared in this embodiment), 3 parts of antioxidant, 1.2 parts of lubricant, and 10 parts of carbon fiber; mix PPO resin, polystyrene, modified flame retardant, modified toughening agent, antioxidant 1010 and N,N-ethylene bisstearamide to obtain a mixed material; S2. Add the mixed material and carbon fiber into a twin-screw extruder for extrusion granulation to obtain a conductive MPPO material based on carbon fiber, wherein the temperature of the twin-screw extruder is set to: zone 1: 190°C, zone 2: 300°C, zone 3: 300°C, zone 4: 300°C, zone 5: 300°C, zone 6: 250°C, zone 7: 250°C, zone 8: 250°C, die head temperature: 270°C, and the screw speed is 500r / min; The modified flame retardant is prepared by the following method: Step A1: 112 mL of toluene, 0.15 mol of aniline, 0.15 mol of 2-allyl-4-methylphenol and 0.3 mol of paraformaldehyde were mixed evenly, stirred thoroughly, heated to 90° C., and reacted for 5 h to obtain an intermediate product; Step A2: 8.64 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 50 mL of N,N-dimethylformamide and 0.04 mol of the intermediate product were mixed, stirred at 150° C. for 9 h, filtered, washed, and dried under vacuum at 60° C. for 24 h to obtain a pre-product; Step A3: 7 g of the pre-product, 7.5 g of tris(hydroxymethyl)aminomethane) and 700 mL of deionized water were mixed, the pH was adjusted to 8.5, 2.4 g of dopamine hydrochloride was added, ultrasonic treatment was performed for 30 min, stirring was performed at room temperature for 24 h, vacuum filtration and washing were performed, and vacuum drying was performed at 60° C. for 24 h to obtain a modified flame retardant; The modified toughening agent is prepared by the following method: Step B1: 0.937 g of tetrakis-(4-aminophenoxy)methylmethane and 5 mL of N-methylpyrrolidone were mixed at 0° C. under nitrogen protection, stirred evenly, and then 0.735 g of maleic anhydride was added, and stirred at 7° C. for 1 h to obtain product a; Step B2: Mix dodecylbenzenesulfonic acid and 45 mL of deionized water, raise the temperature to 45°C, stir evenly, then slowly drop 4 mol of decamethylcyclopentasiloxane and 6 mol of 3-allyloxypropyltrimethoxysilane, mix evenly, react for 3 hours, and cool to room temperature to obtain product b. The amount of dodecylbenzenesulfonic acid used accounts for 1.4% of the total amount of deionized water in the system; Step B3: Mix 6 g of product a and 3 g of product b, stir for 10 min, add 0.43 g of azobisisobutyronitrile and 20 mL of ethanol and mix evenly, heat to 75° C., react for 3 h, and cool to room temperature to obtain a modified toughening agent.

[0014] Embodiment 3: A method for preparing a conductive MPPO material based on carbon fiber, specifically comprising the following steps: S1. Weigh the raw materials by weight: 70 parts of PPO resin, 30 parts of polystyrene, 20 parts of modified flame retardant (prepared in this embodiment), 10 parts of modified toughening agent (prepared in this embodiment), 5 parts of antioxidant, 2 parts of lubricant, and 15 parts of carbon fiber; mix PPO resin, polystyrene, modified flame retardant, modified toughening agent, antioxidant 1010 and N,N-ethylene bisstearamide to obtain a mixed material; S2. Add the mixed material and carbon fiber into a twin-screw extruder for extrusion granulation to obtain a conductive MPPO material based on carbon fiber, wherein the temperature of the twin-screw extruder is set to: zone 1: 200°C, zone 2: 320°C, zone 3: 320°C, zone 4: 320°C, zone 5: 320°C, zone 6: 260°C, zone 7: 260°C, zone 8: 260°C, die head temperature: 280°C, and the screw speed is 600r / min; The modified flame retardant is prepared by the following method: Step A1: 150 mL of toluene, 0.2 mol of aniline, 0.2 mol of 2-allyl-4-methylphenol and 0.4 mol of paraformaldehyde were mixed evenly, stirred thoroughly, heated to 90° C., and reacted for 5 h to obtain an intermediate product; Step A2: 10.8 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 60 mL of N,N-dimethylformamide and 0.05 mol of the intermediate product were mixed, stirred at 150° C. for 9 h, filtered, washed, and dried under vacuum at 60° C. for 24 h to obtain a pre-product; Step A3: 8 g of the pre-product, 10 g of tris(hydroxymethyl)aminomethane) and 900 mL of deionized water were mixed, the pH was adjusted to 8.5, 2.4 g of dopamine hydrochloride was added, ultrasonic treatment was performed for 30 min, stirring was performed at room temperature for 24 h, vacuum filtration and washing were performed, and vacuum drying was performed at 60° C. for 24 h to obtain a modified flame retardant; The modified toughening agent is prepared by the following method: Step B1: 1.25 g of tetrakis-(4-aminophenoxy)methylmethane and 5 mL of N-methylpyrrolidone were mixed at 0° C. under nitrogen protection, stirred evenly, and then 0.98 g of maleic anhydride was added, and stirred at 15° C. for 1 h to obtain product a; Step B2: dodecylbenzenesulfonic acid and 45 mL of deionized water were mixed, the temperature was raised to 45°C, and the mixture was stirred evenly. Then, 5 mol of decamethylcyclopentasiloxane and 7 mol of 3-allyloxypropyltrimethoxysilane were slowly added dropwise, the mixture was mixed evenly, and the mixture was reacted for 3 h. The mixture was cooled to room temperature to obtain product b. The amount of dodecylbenzenesulfonic acid used was 1.4% of the total amount of deionized water in the system. Step B3: Mix 7 g of product a and 4 g of product b, stir for 10 min, add 0.52 g of azobisisobutyronitrile and 20 mL of ethanol and mix evenly, heat to 80° C., react for 3 h, and cool to room temperature to obtain a modified toughening agent.

[0015] Comparative Example 1: This comparative example is a conductive MPPO material based on carbon fiber. The difference from Example 3 is that an equal amount of magnesium hydroxide is used to replace the modified flame retardant prepared in Example 3, and the rest are the same.

[0016] Comparative Example 2: This comparative example is a conductive MPPO material based on carbon fiber. The difference from Example 3 is that an equal amount of silicone oil is used to replace the modified toughening agent prepared in Example 3, and the rest are the same.

[0017] Performance test: The carbon fiber-based conductive MPPO materials prepared in Examples 1-3 and the comparative example were cut into standard test sizes, and the surface resistivity was tested according to the IEC60093 standard; the notched impact strength was tested according to the ASTM D256 standard; the tensile strength was tested according to the ASTM D256638 standard; the heat deformation temperature was tested according to the ASTM D648 standard; the vertical burning performance was tested using the GB / T2048-1996 plastic burning performance test method; the test results are shown in the following table:

[0018] It can be seen from the test data in Table 1 that the carbon fiber-based conductive MPPO material prepared in the present invention has excellent conductivity and impact resistance. It can also be seen from the above table that the carbon fiber-based conductive MPPO material prepared in the present invention has good heat resistance and flame retardant properties.

[0019] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing a conductive MPPO material based on carbon fiber, characterized in that: The specific steps include: S1. Weigh the raw materials by weight: 40-70 parts of PPO resin, 10-30 parts of polystyrene, 5-20 parts of modified flame retardant, 2-10 parts of modified toughening agent, 0.1-5 parts of antioxidant, 0.5-2 parts of lubricant, and 5-15 parts of carbon fiber; mix the PPO resin, polystyrene, modified flame retardant, modified toughening agent, antioxidant and lubricant to obtain a mixed material; S2. Add the mixed material and carbon fiber into a twin-screw extruder for extrusion and granulation to obtain a conductive MPPO material based on carbon fiber, wherein the temperature of the twin-screw extruder is set to: zone 1: 180-200°C, zone 2: 280-320°C, zone 3: 280-320°C, zone 4: 280-320°C, zone 5: 280-320°C, zone 6: 240-260°C, zone 7: 240-260°C, zone 8: 240-260°C, head temperature: 260-280°C, and the screw speed is 400-600r / min.

2. The method for preparing a conductive MPPO material based on carbon fiber according to claim 1, characterized in that: The modified flame retardant is prepared by the following method: Step A1: Mix toluene, aniline, 2-allyl-4-methylphenol and paraformaldehyde evenly, stir thoroughly, heat to 90° C., and react for 5 hours to obtain an intermediate product; Step A2: 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, N,N-dimethylformamide and the intermediate product were mixed, stirred at 150° C. for 9 h, filtered, washed, and vacuum dried at 60° C. for 24 h to obtain a pre-product; Step A3: Mix the pre-product, tris(hydroxymethyl)aminomethane) and deionized water, adjust the pH to 8.5, add dopamine hydrochloride, ultrasonically treat for 30 minutes, stir at room temperature for 24 hours, vacuum filter, wash, and vacuum dry at 60° C. for 24 hours to obtain a modified flame retardant.

3. The method for preparing a conductive MPPO material based on carbon fiber according to claim 2, characterized in that: In step A1, the usage ratio of toluene, aniline, 2-allyl-4-methylphenol and paraformaldehyde is 75-150 mL: 0.1-0.2 mol: 0.1-0.2 mol: 0.2-0.4 mol.

4. The method for preparing a conductive MPPO material based on carbon fiber according to claim 2, characterized in that: In step A2, the usage ratio of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, N,N-dimethylformamide and the intermediate product is 6.48-10.8 g: 40-60 mL: 0.03-0.05 mol.

5. The method for preparing a conductive MPPO material based on carbon fiber according to claim 2, characterized in that: In step A3, the dosage ratio of the pre-product, tris(hydroxymethyl)aminomethane, deionized water and dopamine hydrochloride is 6-8 g: 5-10 g: 500-900 mL: 2.4 g.

6. The method for preparing a conductive MPPO material based on carbon fiber according to claim 1, characterized in that: The modified toughening agent is prepared by the following method: Step B1: Tetrakis-(4-aminophenoxy)methylmethane and N-methylpyrrolidone were mixed at 0°C under nitrogen protection, stirred evenly, and then maleic anhydride was added, and stirred at 0-15°C for 1 hour to obtain product a; Step B2: dodecylbenzenesulfonic acid and deionized water were mixed, the temperature was raised to 45°C, and the mixture was stirred evenly. Then, decamethylcyclopentasiloxane and 3-allyloxypropyltrimethoxysilane were slowly added dropwise, the mixture was mixed evenly, and the mixture was reacted for 3 hours. The mixture was cooled to room temperature to obtain product b. Step B3: Mix product a and product b, stir for 10 minutes, then add azobisisobutyronitrile and ethanol and mix evenly, heat to 70-80° C., react for 3 hours, and cool to room temperature to obtain a modified toughening agent.

7. The method for preparing a conductive MPPO material based on carbon fiber according to claim 6, characterized in that: In step B1, the usage ratio of tetrakis-(4-aminophenoxy)methylmethane, N-methylpyrrolidone and maleic anhydride is 0.625-1.25 g:5 mL:0.49-0.98 g.

8. The method for preparing a conductive MPPO material based on carbon fiber according to claim 6, characterized in that: In step B2, the usage ratio of deionized water, decamethylcyclopentasiloxane, and 3-allyloxypropyltrimethoxysilane is 45 mL: 3-5 mol: 5-7 mol, and the usage of dodecylbenzenesulfonic acid accounts for 1.4% of the total amount of deionized water in the system.

9. The method for preparing a conductive MPPO material based on carbon fiber according to claim 6, characterized in that: In step B3, the usage ratio of product a, product b, azobisisobutyronitrile and ethanol is 5-7 g: 2-4 g: 0.34-0.52 g: 20 mL.

10. A conductive MPPO material based on carbon fiber, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Production method for dihydric phenol type high fire-retardancy benzoxazine resin containing phosphor

    CN101220153A

  • Good-surface highly-filled PPO / PA alloy material and preparation method thereof

    CN108276758A

  • Preparation method and application of organic silicon toughening agent

    CN118126262A

  • Halogen-free flame-retardant TPU composite material and preparation method thereof

    CN119220087A

  • Benzoxazine intermediate containing N-allyl and composition and preparation thereof

    CN1472205A